2005
DOI: 10.1038/sj.bdj.4812047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of professional behaviour — a comparison of self-assessment by first year dental students and assessment by staff

Abstract: Objective: A study was set up to assess usefulness and acceptability of a method of assessing professional behaviour of undergraduate dental students. Setting: The first year preclinical course at the Department of Dentistry and Oral Hygiene, University of Groningen, the Netherlands. Materials and method: A form was developed with an ordinal scale to assess undergraduate professional behaviour. A standard means of carrying out assessment was then undertaken and subsequently used to give feedback to the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
(8 reference statements)
2
25
0
1
Order By: Relevance
“…Assessment of medical students has taken place in both the clinical setting (93, 94) and within problem‐based learning group sessions (95). Dental students have been observed by staff within a skills laboratory, and the observations combined with self‐assessment to provide the students with concrete feedback (96).…”
Section: Assessment Of Professionalismmentioning
confidence: 99%
“…Assessment of medical students has taken place in both the clinical setting (93, 94) and within problem‐based learning group sessions (95). Dental students have been observed by staff within a skills laboratory, and the observations combined with self‐assessment to provide the students with concrete feedback (96).…”
Section: Assessment Of Professionalismmentioning
confidence: 99%
“…The bulk of studies have found that self-evaluation correlates poorly with subsequent performance and therefore conclude that learners' self-evaluation ability is poor (Falchikov and Boud 1989;Gordon 1991;Tracey et al 1997;Wayne et al 2006;Zijlstra-Shaw et al 2005). Suggested influences on accuracy include academic performance (Hodges et al 2001;Violato and Lockyer 2006) and gender, with studies indicating under-rating by women and over-rating by men in comparison to external measures (Mattheos et al 2004;Minter et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Students' self-assessment is the cornerstone of learned skills to ensure optimal patient-centered care learner outcomes. [1][2][3][4][5][6][7][8][9][10] Students' self-assessment is the cornerstone of learned skills to ensure optimal patient-centered care learner outcomes.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Students' self-assessment is the cornerstone of learned skills to ensure optimal patient-centered care learner outcomes. [6][7][8][9] It is imperative to understand the progression of learner outcomes through consistent objectives, so that calibrated and realistic expectations of dental students' clinical experiences are established. Due to this fledgling approach, novice students have a hard time discerning small details that can be detrimental to the longevity of direct restorations.…”
mentioning
confidence: 99%
See 1 more Smart Citation